2022
DOI: 10.1212/wnl.0000000000200968
|View full text |Cite
|
Sign up to set email alerts
|

Time Since Stroke Onset, Quantitative Collateral Score, and Functional Outcome After Endovascular Treatment for Acute Ischemic Stroke

Abstract: Background:In patients with ischemic stroke undergoing endovascular treatment (EVT), time to treatment and collateral status are important prognostic factors and may be correlated. We aimed to assess the relation between time to CT angiography (CTA) and a quantitatively determined collateral score and to assess whether the collateral score modified the relation between time to recanalization and functional outcome.Methods:We analysed data from patients with acute ischemic stroke included in the MR CLEAN Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Our study also confirmed that patients with AIS having good collaterals would have lesser neurological impairment, which was in line with many previous studies ( Berkhemer et al, 2016 ; Anadani et al, 2021 ; Uniken Venema et al, 2022 ). And a patient with a qCS (M3-distal) of < 88.29% would be predicted to have an ominous prognosis, with a cutoff higher than the cutoff vCS (50%) ( Lu et al, 2019 ), even if the tissue perfusion parameters met the criteria for MT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also confirmed that patients with AIS having good collaterals would have lesser neurological impairment, which was in line with many previous studies ( Berkhemer et al, 2016 ; Anadani et al, 2021 ; Uniken Venema et al, 2022 ). And a patient with a qCS (M3-distal) of < 88.29% would be predicted to have an ominous prognosis, with a cutoff higher than the cutoff vCS (50%) ( Lu et al, 2019 ), even if the tissue perfusion parameters met the criteria for MT.…”
Section: Discussionsupporting
confidence: 93%
“…The adjusted OR value (3.36) of vCS in this study was relatively too large, as 1 point increase in vCS corresponded to a 236% better outcome of patients with AIS. The large span, also found in a recent study ( Uniken Venema et al, 2022 ), reinforced the point that vCS was inferior to qCS due to its unrefined categorical method.…”
Section: Discussionsupporting
confidence: 74%
“…We found statistically and clinically significant benefit in functional outcomes and mortality with faster IVT administration before EVT. In concert with previous studies, 5–8 our results demonstrate that faster EVT treatment is associated with more home time and lower mortality during the 1-year follow-up period. Our overall results indicate that IVT-to-EVT times may have a modest association with home time, after controlling for patient and hospital factors.…”
Section: Discussionsupporting
confidence: 89%
“…40 For patients who have EVT within 6.5 hours from stroke onset, the benefit of a shorter time to recanalization is independent of baseline collateral status. 6 The present study only included patients with EVT started within 7 hours of stroke onset in which perfusion imaging was not recommended. However, some patients might still have been selected on the basis of advance imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation